Contribution to the characterization of Opuntia spp. juices by LC–DAD–ESI-MS/MS. (1st November 2016) - Mata, A.; Ferreira, J.P.; Semedo, C.; Serra, T.; Duarte, C.M.M.; Bronze, M.R.
Highlights: Composition of Opuntia ficus-indica juice was characterized by LC–DAD–ESI-MS/MS. Phenolic and phenylpyruvic acids and derivatives were detected. Isorhamnetin derivatives were the dominant flavonol glycosides identified. Six betaxanthins and three betacyanin were detected in the samples. Derivative compounds from piscidic acid were tentatively characterized. Abstract: Opuntia spp. fruits are considered as health promoting foods due to the diversity of bioactive molecules found in these fruits. The composition in organic acids, flavonols and betalains in the Opuntia ficus-indica juice from a region of Portugal was accomplished for the first time by liquid chromatography and tandem mass spectrometry using an electrospray ionization source operating in negative and positive mode. The methodology used allowed the detection of 44 compounds, from which 32 were identified. Isorhamnetin derivatives were the dominant flavonol glycosides. A total of 9 betalains including 6 betaxanthins and 3 betacyanin were also detected in the fruit juice samples and indicaxanthin, betanin and isobetanin were the major pigments. Phenolic acid and phenylpyruvic acid derivatives were also identified. To our knowledge, it is the first time derivative compounds from piscidic acid, phenolic compounds and betalains are characterized in cactus pear juice using a single LC–DAD–ESI-MS/MS method.